Confinement Effects on the Benzene Orientational Structure. Issue 17 (13th March 2018) - Falkowska, Marta; Bowron, Daniel T.; Manyar, Haresh; Youngs, Tristan G. A.; Hardacre, Christopher
Abstract: Liquids under confinement exhibit different properties compared with their corresponding bulk phases, for example, miscibility, phase transitions, and diffusion. The underlying cause is the local ordering of molecules, which is usually only studied using pure simulation methods. Herein, we derive experimentally the structure of benzene confined in MCM‐41 using total neutron scattering measurements. The study reveals a layering of molecules across a pore, and four concentric cylindrical shells can be distinguished for a pore with the radius of 18 Å. The nanoscale confinement of the liquid has a major effect on the spatial and orientational correlations observed between the molecules, when compared with the structure of the bulk liquid. These differences are most marked for molecules in parallel configurations, and this suggests differences in chemical reactivity between the confined and bulk liquids. Abstract : Nanoscale confinement : Benzene molecules confined in pores have a different structure than in the bulk phase. The confined benzene molecules are studied experimentally by total neutron scattering. Discrepancies are marked in molecule–molecule distances and molecule–molecule orientation.